Standard EEG: A Research Roadmap for Neuropsychiatry - Boutros, Nash N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This volume is designed to serve as a reference source containing both historical and recent references with a special focus on the existing gaps of knowledge regarding EEG deviations in psychiatric populations. Every chapter begins by outlining the clinical issues, then reviews available literature and concludes by highlighting a) currently supportable findings, and b) open research questions. In some chapters the author makes suggestions regarding the research design that will most likely lead to generating data that can move the field towards resolving unresolved issues.
Philosophical differences between psychiatric and neurological approaches to the Standard EEG and historical perspective -- What constitutes a normal EEG? Special electrodes -- Effects of psychotropic drugs -- The special case of clozaril -- Abnormal slow rhythms -- Isolated epileptiform discharges -- Clinical EEG and dissociation including panic attacks -- Clinical EEG and aggression -- Clinical EEG and Borderline Personality Disorder -- Clinical EEG and psychotic conditions and affective disorders -- Clinical EEG in psychiatric emergencies.-Clinical EEG and ADHD and learning disability -- Clinical EEG and Autism Spectrum Disorders -- Introduction to the controversial EEG waveforms -- B-Mittens -- Small Sharp Spikes -- The 6/second spike and wave discharges, Rhythmic Mid-temporal Discharges and the Wicket Spikes -- The 14 and 6 positive Spikes -- Afterwords.
Keywords: Medicine; Neurosciences; Neurology; Psychiatry; Biomedicine; Neurosciences; Psychiatry; Neurology